A novel TAB2 mutation detected in a putative case of frontometaphyseal dysplasia - Asuka Hori; Ohsuke Migita; Rika Kawaguchi-Kawata; Yoko Narumi-Kishimoto; Fumio Takada; Kenichiro Hata (Human Genome Variation, 2021)
Abstract Frontometaphyseal dysplasia (FMD) type 2 is an autosomal dominant disorder characterized by skeletal abnormalities and caused by MAP3K7 mutation. We identified a novel missense mutation in TAB2 associated with FMD in a child with multiple congenital malformations. This case was diagnosed as FMD due to joint contractures and bone deformities. This is the third report of FMD caused by a TAB2 mutation located in the TAK1-binding region.